2013
DOI: 10.1172/jci66369
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic stellate cells in liver development, regeneration, and cancer

Abstract: Hepatic stellate cells are liver-specific mesenchymal cells that play vital roles in liver physiology and fibrogenesis. They are located in the space of Disse and maintain close interactions with sinusoidal endothelial cells and hepatic epithelial cells. It is becoming increasingly clear that hepatic stellate cells have a profound impact on the differentiation, proliferation, and morphogenesis of other hepatic cell types during liver development and regeneration. In this Review, we summarize and evaluate the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
567
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 595 publications
(593 citation statements)
references
References 113 publications
10
567
0
6
Order By: Relevance
“…Both the cell purity and viability exceeded 95%. Cells cultured for 1-2 days were used as quiescent HSCs (qHSCs), which do not proliferate, contain vitamin A in lipid droplets, and express GFAP but not collagen (3,13). HSCs subcultured for 4 -5 days transdifferentiate spontaneously into activated myofibroblast-like cells, used as aHSCs, which proliferate to induce fibrosis and express ␣SMA, gp46, and collagen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the cell purity and viability exceeded 95%. Cells cultured for 1-2 days were used as quiescent HSCs (qHSCs), which do not proliferate, contain vitamin A in lipid droplets, and express GFAP but not collagen (3,13). HSCs subcultured for 4 -5 days transdifferentiate spontaneously into activated myofibroblast-like cells, used as aHSCs, which proliferate to induce fibrosis and express ␣SMA, gp46, and collagen.…”
Section: Methodsmentioning
confidence: 99%
“…They are characterized by the specific feature of taking up vitamin A and depositing it as intracytoplasmic droplets. Recent studies revealed an additional important characteristic of stellate cells in the liver: a pivotal role in liver regeneration (2,3). Despite the diffuse distribution of stellate cells, most detailed investigations of their character have been carried out with cells of hepatic origin.…”
mentioning
confidence: 99%
“…Mesenchymal cells are known to have a critical role in liver regeneration. Stellate cells, fibroblasts, endothelial and kupffer cells are the main types of mesenchymal cells in the liver as well as the sources of growth factors during liver regeneration [3][4][5]. Following acute injury, hepatocytes release mitogenic signals to mesenchymal cells and induce their activation and proliferation.…”
Section: Liver Regeneration and Progenitor Cell Activationmentioning
confidence: 99%
“…Upon transient amplification, these HPCs infiltrate along the liver plate toward the central vein and differentiate into hepatocytes to restore liver function and cell mass [47,48]. Despite all of these studies, the origin of progenitor cells and their migration during liver regeneration remains unclear [3][4][5]. Fibroblast progenitor cells are known to contribute to liver regeneration via activation of Hedghog signaling [49].…”
Section: Liver Regeneration and Progenitor Cell Activationmentioning
confidence: 99%
See 1 more Smart Citation